Widening Free Choice - Willer, Malte (Proceedings of the Amsterdam Colloquium, 2017)
Disjunctions scoping under possibility modals give rise to the free choice effect. The effect also arises if the disjunction takes wide scope over possibility modals; it is independent of the modal flavor at play (deontic, epistemic, and so on); and it arises even if disjunctions scope under or over necessity modals. At the same time, free choice effects disappear in the scope of negation or if the speaker signals ignorance or unwillingness to cooperate. I show how we can account for this wide variety of free choice observations without unwelcome side-effects in an update-based framework whose key innovations consist in (i) a refined test semantics for necessity modals and (ii) a generalized conception of narrow and wide scope free choice effects as arising from lexically or pragmatically generated prohibitions against the absurd state (an inconsistent information carrier) serving as an update relatum. The fact that some of these prohibitions are defeasible together with a binary semantics that distinguishes between positive and negative update relata accounts for free choice cancellation effects.